2014
DOI: 10.1039/c4nr03396e
|View full text |Cite
|
Sign up to set email alerts
|

Copper metal–organic framework nanocrystal for plane effect nonenzymatic electro-catalytic activity of glucose

Abstract: This work describes the first demonstration of nanocrystal plane dependent nonenzymatic electro-catalytic glucose activity of [Cu3(btc)2] nanocrystals with different shapes (nanocube, truncated cube, cuboctahedron, and octahedron). From electrochemical results, the obtained [Cu3(btc)2] nanocube modified electrode shows the best nonenzymatic electro-catalytic glucose activity. Interestingly, decreasing the {100} crystal planes from cubes to octahedra, changes the nonenzymatic electro-catalytic activity from hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Cu‐based materials generally do not determinate the glucose in acid or neutral media because the production of sensing element (Cu(III)) is greatly dependent on the OH − concentration in electrolyte . An unexpected, interesting discovery in our work is that Cu 2 (NDC) 2 /PDHP possesses moderate glucose sensing ability in acid media.…”
Section: Resultsmentioning
confidence: 79%
“…Cu‐based materials generally do not determinate the glucose in acid or neutral media because the production of sensing element (Cu(III)) is greatly dependent on the OH − concentration in electrolyte . An unexpected, interesting discovery in our work is that Cu 2 (NDC) 2 /PDHP possesses moderate glucose sensing ability in acid media.…”
Section: Resultsmentioning
confidence: 79%
“…In addition to the aforementioned applications, many Cu-MOFs and Cu-MOF composites have also exhibited high catalytic activities in other electrochemistry reactions, such as the ethanol oxidation reaction, [102] hydrogen peroxide oxidation reaction, [103] hydrazine oxidation reaction, [104] non-enzymatic electrocatalysis of glucose, [105,106] etc. solution (pH = 6.0) with different rotation rates at a scan rate of 2 mV s À 1 .…”
Section: Cu Mofs and Their Composites For Other Electrochemical Reactmentioning
confidence: 99%
“…By changing the quantity of surfactant cetyltrimethylammonium bromide (CTAB) and keeping other conditions, we adjusted the morphology of copper metal-organic framework nanocrystal and sought for the best proportion. [14] Among four kinds of [Cu 3 (btc) 2 ] nanocrystals, we found that the glassy carbon electrode (GCE), modified by nanocubes with porous 6 {100} facets, demonstrated superior electro-catalytic glucose activity. It was endowed with a couple of advantages such as high sensitivity, low detection limit and great special selectivity.…”
Section: For Non-enzymatic Glucose Detectionmentioning
confidence: 99%